Realising Social Harmony Through Religious Moderation in Indonesia's Multicultural Era - Yusep Arimatea; Timotius Sukarna (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Indonesia is a unitary state with a lot of diversity, including various tribes, languages, religions, and cultures. Because it has so many differences, it is important for this nation to practice moderation in religion in order to prevent divisions that can damage the unity of the country. This research is educational and empirical. From the educational aspect, the focus is on the social aspect of religion in a multicultural society by emphasising the values of moderation. Meanwhile, from the empirical side, researchers will analyse the behaviour and actions of society in the practice of religious moderation. A country that is rich in diversity like Indonesia today often faces the issue of radicalism. Various groups that claim to represent certain interests are growing and openly spreading their ideologies. Therefore, religious moderation is an important element to encourage mutual understanding and respect for differences. It is hoped that this can be realised in harmony between religious communities in the midst of community life. The main objective of this study is to explore how to implement religious moderation as a strategic step to create a more inclusive and harmonious Indonesia in the future. The approach used in this study is a literature review, with a descriptive analysis style, namely examining documents and the implementation of religious moderation programmes in Indonesia. The results of the study show that the government faces various challenges in implementing religious moderation, such as rejection from conservative groups and lack of support from educational institutions. The conclusion of this study is that religious moderation is a key factor in building a harmonious and inclusive Indonesia. This can be achieved by increasing collaboration between the government, religious leaders, and the community in promoting the values of moderation. Thus, religious moderation can be a strong foundation for ensuring peace and social stability in Indonesia.